Life Cycle Costing Analyses of Offshore Substructure Options: Pile-On-Water V Floating-Substructure V Traditional-Land-Option - Whyte, Andrew; Gajda, Philip (Research Publishing, 2011)
This work develops, then applies, an offshore-specific life-cycle-costing analysis (LCCA) technique able to compare three alternate substructure options for an asset constructed on the Swan River near the Perth Central Business District, Western Australia; the results generated provide stakeholder guidance in choosing between alternative specifications. Substructure alternative designs analysed for whole-life were: a pile on water substructure option; a reinforced concrete floating substructure; and, a traditional land-based substructure design. A qualitative case-study analysis towards a decision-making guide is described and encompasses: design, construction, maintenance, and disposal. The findings of the life-cycle costing analysis conducted argue that, given a choice of several alternatives, the lowest net-present-value over a life-span study-period of 30 years is a pile-on-water substructure option; this is found to be the most economically viable alternative in lieu of other specification solutions. The work presented here argues that life cycle costing analysis is an invaluable tool for designers and stakeholders, to determine the true costs of development/design alternatives in a decision making process, where several, technically-viable, design solutions are available.